2020
DOI: 10.52434/jfb.v11i1.698
|View full text |Cite
|
Sign up to set email alerts
|

AKTIVITAS ANTIOKSIDAN BUAH PINING (Hornstedtia alliacea) DENGAN MENGGUNAKAN METODE DPPH

Abstract: Indonesia merupakan negara kepulauan yang berada pada zona khatulistiwa dan terkenal memiliki keanekaragaman jenis tanaman, tetapi potensi ini belum semuanya dapat dimanfaatkan sebagai bahan industri khususnya tanaman berkhasiat obat. Buah Pining (Hornstedtia alliacea) merupakan tanaman yang masih sedikit dimanfaatkan dalam bidang kesehatan dikarenakan masih minimnya informasi mengenai fitokimia dari tanaman tersebut. Dilakukan skrining fitokimia tanaman buah pining (Hornstedtia alliacea), untuk mengetahui kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…However, apart from flavonoids and terpenoids, this research also found other secondary metabolite compounds, namely alkaloids and quinones. 13 Differences in plant secondary metabolite content can be influenced by differences in growing areas, altitude, rainfall and soil nutrient conditions. 15 Flavonoids contain aromatic groups which, when reacted with bases, will conjugate and form a yellow color.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, apart from flavonoids and terpenoids, this research also found other secondary metabolite compounds, namely alkaloids and quinones. 13 Differences in plant secondary metabolite content can be influenced by differences in growing areas, altitude, rainfall and soil nutrient conditions. 15 Flavonoids contain aromatic groups which, when reacted with bases, will conjugate and form a yellow color.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the description of several research results, the author conducted this research to determine whether giving Galoba fruit extract which contains secondary metabolite compounds as an exogenous antioxidant can affect MDA levels in the serum of hyperglycemic mice. 13…”
Section: Introductionmentioning
confidence: 99%
“…Galoba (Hornstedtia alliacea) merupakan salah satu buah lokal Maluku yang memiliki ciri berbentuk lonjong, kulit buahnya berwarna coklat, sedangkan salut daging buah berwarna hitam dan buah ini memiliki rasa manis dengan kombinasi berasa agak asam. Gustaman et al (2020), mengemukakan bahwa galoba mengandung senyawa metabolit sekunder diantaranya flavonoid, kuinon, monoterpen dan seskuiterpen serta memiliki aktivitas antioksidan sebesar 23,43 ppm. Pemanfaatan galoba di daerah Maluku masih terbatas, pada umumnya masyarakat mengkonsumsinya dalam bentuk segar, belum dilakukan pengolahan lanjut dari buah tersebut.…”
Section: Pendahuluanunclassified